Policies to Encourage the Use of Biosimilars in European Countries and Their Potential Impact on Pharmaceutical Expenditure - Vogler, Sabine; Schneider, Peter; Zuba, Martin; Busse, Reinhard; Panteli, Dimitra (Frontiers in Pharmacology, 2021)
Introduction: Biosimilar medicines are considered promising alternatives to new biologicals with high price tags. The extent of savings resulting from biosimilar use depends on their price and uptake, which are largely shaped by pricing, reimbursement and demand-side policies. This paper informs about different policy measures employed by European countries to design the biologicals market and explores potential savings from the increased use of biosimilar medicines in Germany. Methods: Policy measures that target the price and uptake of biosimilar medicines were identified based on a prefilled questionnaire survey with public authorities in 16 European countries, who were members of the Pharmaceutical Pricing and Reimbursement Information (PPRI) network (July 2020). Potential savings that could have been generated in Germany if different measures identified in the surveyed countries had been implemented were calculated for six publicly funded biological molecules. Price data of the Pharma Price Information (PPI) service and German consumption data for 2018 were used for the calculation of five scenarios. Results: Several countries use a price link policy, setting the biosimilar price as a percentage of the price of the reference biological. Also lowering the price of the reference biological upon market entry of a biosimilar is less frequently used. While tendering of biosimilar medicines in the inpatient setting is the norm, it is rarely employed for biosimilars in outpatient use. Reference price systems and INN-prescribing of medicines are commonly used policy measures in the off-patent market, but some countries define exemptions for biologicals. Substituting biosimilars at the pharmacy level is rather an exception. Potential savings in Germany ranged from 5% (simple price link) to 55% (prices at the level of other countries) for the six studied molecules Conclusions: Despite some differences, there are discernible tendencies across European countries with regard to their application of certain policy measures targeting the price and uptake of biosimilar medicines. The potential for savings of some of these policies was clearly demonstrated. Monitoring and evaluation of these rather recent measures is key for obtaining a more comprehensive picture of their impact.